Two new species of Nazeris Fauvel in the Luoxiao Mountain Range, China(Coleoptera, Staphylinidae, Paederinae) - Hu, Jia-Yao; Liu, Yi-Xiao; Li, Li-Zhen (Zootaxa, 2018)
Six species of the genus Nazeris Fauvel, 1873 are recorded in the Luoxiao Mountain Range, China. Two of them are described: N. yipingae sp. n. and N. jiaweii sp. n. Nazeris xiaobini Hu & Li, 2015 and N. rufus Hu & Li, 2015 are newly recorded from Hubei Province. An identification key to the Nazeris species in this area and a map showing their distribution are given.